Risk Factors of the Incidence of Pulmonary Tuberculosis in Banjarmasin City, Kalimantan, Indonesia - Farida Heriyani; Adi Heru Husodo; Yusrizal Djam′an Saleh (Intelektual Pustaka Media Utama, 2013)
Pulmonary tuberculosis remains a major cause of morbidity and mortality in the world, including Indonesia. In South Kalimantan, an increasing incidence of tuberculosis up to the year 2010 which were taken using a smear-positive reached 3,237 cases, the largest was in Banjarmasin City which reached 642 cases and the detection rate still low, which is 52, 1%. To investigate the relationship among environmental risk factors of the house (residential density, the air temperature, humidity, ventilation, and natural lighting), smoking behavior and alcohol consumption among tuberculosis patients with the incidence of pulmonary tuberculosis in Banjarmasin City. This study was an analytic observational with case control study. The subjects were tuberculosis patients with smear-positive as a case group and smear-negative as a control group. Residential density, the air temperature, ventilation, natural lighting, smoking behavior and alcohol consumption significantly associated with the incidence of pulmonary tuberculosis in Banjarmasin City. While the humidity was not significantly associated. The most dominant risk factors in the incidence of pulmonary tuberculosis in Banjarmasin City were inappropriate of the air temperature in subjects with a history of household contact with tuberculosis patient, natural lighting, and house ventilation.DOI: http://dx.doi.org/10.11591/ijphs.v2i1.1483